The Reaction of Cs2[Tc(NO)F5] with BF3 in Acetonitrile: Formation and Structure of [Tc(NO)(CH3CN)42(μ‐F)](BF4)3. Issue 18 (24th August 2017) - Balasekaran, Samundeeswari Mariappan; Hagenbach, Adelheid; Spandl, Johann; Abram, Ulrich
Abstract : The deep blue, paramagnetic Cs2 [Tc II (NO)F5 ] is formed during reactions of pertechnetate, acetohydroxamic acid, and CsF in aqueous HF. A reaction of Cs2 [Tc(NO)F5 ] with BF3 · MeOH in acetonitrile gives yellow blocks of the fluorido‐bridged dimer [Tc I (NO)(CH3 CN)4 2 F](BF4 )3 . The compound is stable as solid and in acetonitrile solutions. The complex cation contains a bent μ‐F – ligand and two linear nitrosyl groups. Abstract :